Impact of induction agents and maintenance immunosuppression on torque teno virus loads and year-one complications after kidney transplantation - Reineke, Marvin; Speer, Claudius; Bundschuh, Christian; Klein, Julian A. F.; Loi, Lisa; Sommerer, Claudia; Zeier, Martin; Schnitzler, Paul; Morath, Christian; Benning, Louise (Frontiers in Immunology, 2024)
BackgroundTorque teno virus load (TTVL) is gaining importance as a surrogate parameter to assess immunocompetence in kidney transplant recipients. Although the dynamics of TTVL have been investigated before, the impact of different induction agents and variations in immunosuppressive maintenance therapies on TTVL remain unknown.MethodsIn this retrospective study, TTVL was quantified in 537 plasma or serum samples from 134 patients transplanted between 2018 and 2021. TTVL was examined pre-transplantation and 30-, 90-, 180-, and 360-days post-transplant. To assess the influence of induction therapy on TTVL, 67 patients receiving anti-thymocyte globulin (ATG) induction were matched with 67 patients receiving an interleukin-2 receptor antagonist (IL2-RA) induction in terms of age, sex, and donor modality.ResultsFollowing transplantation, there was a steep increase in TTVL post-transplant for all patients with peak viral loads at 90 days post-transplant (median TTVL [IQR] 7.97×106, [4.50×105–1.12×108]) followed by subsequently declining viral loads. Compared to patients receiving IL2-RA as induction therapy, patients receiving ATG had significantly higher peak viral loads 3 months post-transplant (median TTVL [IQR] 2.82×107 [3.93×106–1.30×108] vs. median TTVL [IQR] 2.40×106 [5.73×104–2.60×107]; P<0.001). Throughout all post-transplant time points, patients receiving additional rituximab for induction along with higher tacrolimus target levels exhibited the highest TTVL.Patients whose TTVL 3-months post-transplant exceeded the currently proposed cutoff to predict infections within the first year post-transplant [6.2 log10] showed a trend towards a higher risk of being hospitalized with an infection in the following 9 months, albeit without being statistically significant (HR=1.642, P=0.07).ConclusionsHigher TTVL reflects the greater immunosuppressive burden in immunological high-risk patients receiving intensive immunosuppression. The choice of induction agent and intensified immunosuppressive maintenance therapy notably affects TTVL at 3 months post-transplant and beyond, necessitating careful consideration when interpreting and applying TTVL cutoffs to monitor immunocompetence post-transplant.